Engineering Advances in Modern Drug Delivery Devices: Current Technologies, Challenges, and Future Directions - Suryanarayana Regulagadda; Thrimurthulu Gode; V. S.A. Pavan Rudhrabatla; Taraka Rama Prasadu Vasa; Shiva Reddy Padigapaty; Lakshmi Prasanna Nalluri (Clinical Medicine and Integrative Therapies, 2026)
Background: The expansion of biologics, Gene therapies and personalized medicine has been significant ever since it was initiated in the late 20th century which created an immediate need for advanced drug delivery platforms that could enhance therapeutic output, improve patient compliance and precision-in-treatment. So far, traditional routes of oral and parenteral administration are commonly hampered by limited bioavailability, systemic adverse effects, and poor patient compliance; thus, driving next-generation delivery technologies. Key Technologies Reviewed: The aim of this review is to critically evaluate state-of-the-art developments in drug delivery devices and systems-including prefilled syringes (PFSs) and autoinjectors; inhalation-based delivery platforms; microneedle (MN) patches; nanoparticle-enabled delivery systems; tissue-engineered scaffolds; and advanced transdermal technologies. These platforms are engineered to address biological limitations, improve site-specific drug targeting, and facilitate minimally invasive or self-administered therapies. Engineering and Clinical Aspects: Great strides have been made with respect to advances in device engineering, biomaterials, particle design, microfabrication and digital health integration. However, autoinjectors and very recently prefilled syringes have emerged as the devices of choice for improving dosing accuracy and patient convenience; inhalation systems and MN technologies have offered new options for non-invasive delivery. Nanoparticle-based platforms have shown improved targeting and controllable delivery of therapeutics, especially for complex therapies. The drug delivery device market worldwide is anticipated to exceed due USD 450 billion by the year 2030, a reflection of how clinically relevant these technologies have become. Future Outlook: Among current innovations, the most transformative advances in minimally invasive delivery uses MN systems and nanoparticle-enabled precision delivery to overcome significant barriers of bioavailability, therapeutic targeting and patient acceptability. Nonetheless, large-scale manufacturing, long-term safety assessment, regulatory harmonization and cost-effective commercialization still represent some of the main hurdles towards broader clinical translation. Future technologies will be dependent on the incorporation of artificial intelligence, smart sensors and customized manufacturing strategies to progress towards precision medicine and patient-centered health care.